Liberal Democratic Institutions and the Damages of Political Corruption - Ceva, Emanuela; Ferretti, Maria (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
This article contributes to the debate concerning the identification of politically relevant cases of corruption in a democracy by sketching the basic traits of an original liberal theory of institutional corruption. We define this form of corruption as a deviation with respect to the role entrusted to people occupying certain institutional positions, which are crucial for the implementation of public rules, for private gain. In order to illustrate the damages that corrupt behaviour makes to liberal democratic institutions, we discuss the case of health care professionals’ abuse of their right to conscientious objection to abortion services. We show that the conscience clause can be instrumentally abused to sabotage democratically established public rules and thus exert undue private influence on their implementation. In this sense, from a liberal democratic perspective, institutional corruption is problematic because it is disruptive of such fundamental liberal ideals as the impartiality of public institutions and citizens’ political equality.